2022
DOI: 10.3892/ijo.2022.5323
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated RRS1 inhibits invasion and metastasis of BT549 through RPL11‑c‑Myc‑SNAIL axis

Abstract: Regulator of ribosome synthesis 1 (RRS1) is a key factor in ribosome biosynthesis and other cellular functions. High level of RRS1 in breast cancer cell lines is associated with increased cell proliferation, invasion and migration. RRS1 controls the assembly of the 60s subunit and maturation of 25S rRNA during ribosome biosynthesis. In this study, lentiviral transfection of sh-RNA was used to knock down the level of RRS1, to detect the effect of RRS1 on cell function and to explore the specific mechanism of RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Increased ribosome biogenesis is necessary to maintain the elevated proliferation rate of tumor cells [ 34 ]. Recent research has implicated RRS1 in the development of several malignancies and it is significantly upregulated in various tumors [ 35 , 36 , 37 , 38 ]. The results of our previous studies have demonstrated the function of RRS1 in the growth of BC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ribosome biogenesis is necessary to maintain the elevated proliferation rate of tumor cells [ 34 ]. Recent research has implicated RRS1 in the development of several malignancies and it is significantly upregulated in various tumors [ 35 , 36 , 37 , 38 ]. The results of our previous studies have demonstrated the function of RRS1 in the growth of BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The GV492-GFP and GV115-EGFP lentiviral expression system (Shanghai GeneChem Co., Ltd.) was utilized for the transfection of cells expressing shRNA targeting RRS1 (sh-RRS1), control shRNA (sh-CON), scrambled control (OE-CON), and overexpressed RRS1 (OE-RRS1). The cells were subjected to infection with the corresponding lentiviruses at a multiplicity of infection (MOI) of 20 [ 37 , 38 ]. When the cells reached 20% to 30% confluence, they were transfected with the virus and Hitrans A&P (Shanghai GeneChem Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…RRS1 can promote the development of HCC by enhancing ribosome biogenesis and attenuating RPL11-MDM2-P53 signaling ( 48 ). Furthermore, RRS1 may augment breast cancer cell invasion and metastasis via the RPL11-c-Myc-SNAIL axis ( 49 ). Also, the downregulation of lncRNA SET-binding factor 2-antisense RNA1 can upregulate miR-143 and inhibit RRS1 and ultimately restrict the progression of breast cancer ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, RPL11 reduces H4 acetylation at MYC target promoters inhibiting MYC-mediated transactivation. As RPL11 also affects MYC expression itself and vice versa, they function as a negative feedback loop ( Figure 1 C) [ 24 , 25 , 26 ]. In addition to ribosome biogenesis, MYC can modulate the isoform composition of RNA polymerase III, favoring the expression of the alpha isoform (POLR3G), which has a higher transcriptional potential.…”
Section: Overview Of Myc Regulation In the Physiological Statementioning
confidence: 99%